The Human Condition and Nature’s Reflection in 'The Minister's Black Veil' - Taufan Saputra; Nurholis Nurholis (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
This research delves into the intricate connection that exists between the human condition and the reflection of nature. Through a nearby investigation of the text, this examination intends to reveal how Hawthorne complicatedly winds around together components of imagery and story to depict hidden presences - a figurative investigation of the intricacies of human life and its collaboration with the regular world. The narrative delves into the depths of individual consciousness while simultaneously reflecting the sublime beauty and mystery of nature, drawing on themes of isolation, morality, and societal norms. This study sheds light on the larger cultural and philosophical implications of the narrative by contrasting Hawthorne's portrayal with Wordsworth's philosophical perspectives on human existence and nature."